Extraction kinetic model of polysaccharide from Codonopsis pilosula and the application of polysaccharide in wound healing. (1st March 2022) - Wang, Chenliang; Zhang, Yuchun; Xue, Hongyan; Yang, Mingjun; Leng, Feifan; Wang, Yonggang
Abstract: The crude polysaccharide (CPNP) of Codonopsis pilosula was obtained by hot-water extraction technology. The extraction kinetic model established according to Fick's first law of diffusion and related parameters of polysaccharide was studied. CPNP microcapsules were prepared by blending with sodium alginate, Ca 2+ ions and crude CPNP. The quality control (drug loading rate, embedding rate and release rate, etc) of CPNP microcapsules were analyzed by pharmacopeas standards. The structure feature of CPNP microcapsules also were determined with various methods. The wound healing ability of CPNP microcapsules loading with different concentration of CPNP was evaluated using the rat wound model. The activity of various enzymes and the expression levels of pro-inflammatory factors in the model skin tissue also were determined by enzyme linked immunosorbent assay (ELISA). Hematoxylin-eosin staining (HE), Masson, immunohistochemistry were used to investigate the external application effect of CPNP microcapsules on skin wound repair. The extraction kinetics of CPNP was established with the linear correlation coefficient (R 2 ) of 0.83–0.93, implied that the extraction process was fitted well with the Fick's first law of diffusion. The CPNP has good compatibility with sodium alginate and Ca 2+ ions by SEM and TEM observation, and the particle size of CPNP microcapsules was 21.25 ± 2.84 μm with the good degradation rate, loading rate (61.59%) and encapsulation rate (55.99%), maximum swelling rate (397.380 ± 25.321%). Compared with control group, the redness, and swelling, bleeding, infection, and exudate of the damaged skin decreased significantly after CPNP microcapsules treatment, and the CPNP microcapsules groups exhibited good wound healing function with less inflammatory cell infiltration. The pathological structure showed that in the CPNP microcapsules group, more newborn capillaries, complete skin structure, and relatively tight and orderly arrangement of collagen fibers were observed in the skin of rats. CPNP microcapsules could effectively inhibit the high expression of pro-inflammatory factors in damaged skin, and significantly increase the contents of related enzymes (GSH-Px, T-AOC, LPO) and collagen fibers. The relative expression levels of genes (VEGF and miRNA21) in the CPNP microcapsules group were higher than those in the model group and the negative group. The above results suggested that the CPNP microcapsules could controlled-release the CPNP to the wound surface, and then played a better role in antibacterial, anti-inflammatory and skin wound repair.